Pengaruh Literasi Keuangan, Akses Modal, Dan Motivasi Pelaku Usaha Terhadap Peningkatan Kinerja Usaha Pada UMK Di Kecamatan Buleleng - Dewi, Nyoman Aprilia Kartika; Wahyuni, Made Arie (Universitas Pendidikan Ganesha, 2024)
This research aims to determine the influence of financial literacy, access to capital, and motivation of business actors on improving the performance of Micro and Small Enterprises in Buleleng District. The independent variables in this research are Financial Literacy, Access to Capital, and Motivation of Business Actors and the dependent variable in this research is increased business performance. The population in this study was 1,346 Micro and Small Enterprises in Buleleng District using sampling techniques, namely convenience sampling and the Slovin formula. The number of respondents in this research was 226 business actors. Sample collection in this study used a questionnaire that was measured using a Likert scale and the questionnaire was distributed using two methods, namely visiting the business premises directly and sending the questionnaire using Google Form via the WhatsApp application. The types of data used in this research are primary data and secondary data. Primary data in this research was obtained through the results of filling out questionnaires by respondents and secondary data in this research was data obtained from the Department of Trade, Industry and Cooperatives, Micro and Small Enterprises in Buleleng District. The data analysis technique in this research is multiple linear regression analysis using SPSS v.23 for Windows. From the tests carried out, the results showed that (1) Financial literacy has a positive and significant effect on increasing business performance, (2) Access to capital has a positive and significant effect on increasing business performance, and (3) Motivation of business actors has a positive and significant effect on increasing business performance.paragraf.